2014
DOI: 10.1044/1092-4388(2013/12-0403)
|View full text |Cite
|
Sign up to set email alerts
|

Preterm and Term Infants' Perception of Temporally Coordinated Syllable–Object Pairings: Implications for Lexical Development

Abstract: These findings suggest that even near-term preterm infants present with a delay in their sensitivity to synchrony in syllable–object pairings relative to term infants. Given the important role that synchrony plays in word mapping at 6–9 months, this early delay in sensitivity to synchrony might be an indicator of word mapping delays found in older preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Furthermore, difficulties appear to persist, to some degree, with only small improvements noted in visual recovery to an auditory syllable, but no improvements for visual object changes after 2 months. Thus, from such results it has been argued that early auditory dominance, which gives way to greater multisensory integration in term infants, persists in preterm infants (Gogate et al, 2014). If this is the case, biases in attention, learning, and memory for multisensory information in early development are likely different for preterm infants compared to term infants.…”
Section: Translational Relevance To Studying Multisensory Processingmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, difficulties appear to persist, to some degree, with only small improvements noted in visual recovery to an auditory syllable, but no improvements for visual object changes after 2 months. Thus, from such results it has been argued that early auditory dominance, which gives way to greater multisensory integration in term infants, persists in preterm infants (Gogate et al, 2014). If this is the case, biases in attention, learning, and memory for multisensory information in early development are likely different for preterm infants compared to term infants.…”
Section: Translational Relevance To Studying Multisensory Processingmentioning
confidence: 95%
“…For example, Pickens and colleagues (1994) showed an atypical pattern of development in integrating synchronous face and voice information among preterm infants (see also Lawson, Ruff, McCarton-Daum, Kurtzberg, and Vaughan, 1984 for example with object-sound integration). More recently, Gogate, Maganti, and Perenyi (2014) showed that preterm infants have difficulty temporally binding changes to synchronous syllable-object pairings and that these difficulties are not solely due to attentional deficits. Furthermore, difficulties appear to persist, to some degree, with only small improvements noted in visual recovery to an auditory syllable, but no improvements for visual object changes after 2 months.…”
Section: Translational Relevance To Studying Multisensory Processingmentioning
confidence: 99%
“…Their fragile neurosensory system was likely overwhelmed by the word–object mapping context, where mothers often used synchronous naming especially to younger infants. Their delayed perception (of synchrony, Gogate et al, ; face–voice synchrony, Pickens et al, ; Imafuku et al, ) implies a missed opportunity to learn word–object relations from mothers at both visits, requiring alternate learning mechanisms (Gogate & Hollich, ). Mothers reported a receptive vocabulary in their preterm infants of 12 months (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…If successful, this would provide the first measure of intersensory processing that could be utilized across a variety of populations and ages without changes to the protocol. It could be used to characterize intersensory processing in children who show impairments, including children with ASD (Bebko et al, 2006; Stevenson et al, 2014), children born preterm (Gogate et al, 2014; Pickens et al, 1994), and children with dyslexia (Hairston, Burdette, Flowers, Wood, & Wallace, 2005). Because the IPEP provides both social and nonsocial events, it can identify processing impairments specific to social events.…”
Section: Discussionmentioning
confidence: 99%
“…We included both social (women speaking) and nonsocial (objects impacting a surface) events because they serve as a foundation for language, cognitive, and social development and children with autism show selective impairments in perception of social events, but relatively spared performance with nonsocial events (Dawson, Meltzoff, Osterling, Rinaldi, & Brown, 1998; Patten et al, 2016; Swettenham et al, 1998). Pre-term infants may demonstrate a similar pattern of impairments in intersensory matching for social but not nonsocial events (Gogate, Maganti, & Perenyi, 2014; Pickens et al, 1994; Provasi, Lemoine-Lardennois, Orriols, & Morange-Majoux, 2017). …”
Section: Current Studymentioning
confidence: 99%